Of All Things the Measure is Man: Automatic Classification of Emotions and Inter-labeler Consistency - Steidl, Stefan; Levit, Michael; Batliner, Anton; Noth, Elmar; Niemann, Heinrich (Proc. of ICASSP, 2005)
In traditional classification problems, the reference needed for training a classifier is given and considered to be absolutely correct. However, this does not apply to all tasks. In emotion recognition in non-acted speech, for instance, one often does not know which emotion was really intended by the speaker. Hence, the data is annotated by a group of human labelers who do not agree on one common class in most cases. Often, similar classes are confused systematically. We propose a new entropy-based method to evaluate classification results taking into account these systematic confusions. We can show that a classifier which achieves a recognition rate of “only” about 60 % on a four-class-problem performs as well as our five human labelers on average.